Audience’s Motives and Gratification in Listening to The Podcast - Dian Lestari Meidina; Nani Kurniasari (COMMENTATE: Journal of Communication Management, 2022)
This research aims to find out how much the level of audience satisfaction in listening to the podcast. The researcher views this research based on the positvism paradigm with the quantitative descriptive method approach and the uses and gratification theory. The technique sampling in this research uses non probability sampling technique with available sampling / convenience sampling types. The results of the analysis using paired t test, it is known that the gap contained in the Gratification Sought and Gratification Obtained variables has a significant value indicating a significant difference between the GS variable and the GO variable, and it is known from the results of the study that 385 respondents obtained the results of GS> GO (Media not satisfying the audience), even though in theory the expectancy value that Palmgreen satisfaction-satisfaction created from each indicator is fairly high, overall satisfaction obtained by the audience in listening to the podcast has a satisfaction value above 99%.